A Study On The Effect Of a-Cordierite Ceramic Powder As A Filler In Denture Base Poly (Methyl Methacrylate) - Shawi, Hoaida. K. Salem (2011)
The aim of this research is to investigate on the effect of α-cordierite ceramic powder reinforcement filler in poly methyl methacrylate (PMMA). In this study the formulation used include PMMA, α-cordierite ceramic powder, benzoyl peroxide (BPO) as the initiator, methyl methacrylate as the monomer and ethylene glycol dimethyl acrylate (EGDMA) as the cross-linking agent. The α-cordierite was treated with a silane coupling agent (γ-MPS) before it was mixed with the powder components (PMMA, BPO). The samples are prepared according to the standard dental laboratory application.